Politicizing Europe in Elections to the European Parliament (1994–2019): The Crucial Role of Mainstream Parties - Daniela Braun; Edgar Grande (JCMS: Journal of Common Market Studies, 2021)
Based on original data, this article analyses the politicization of European issues in European elections. Contrary to scholarly expectations, our findings show a higher level of politicization of European issues compared to national elections. However, politicization has been declining in both electoral arenas from the early 2000s until 2014 despite the increasing visibility of radical Eurosceptic parties. This paper suggests that this decline in politicization is a consequence of relatively low levels of emphasis put on the EU issue by mainstream political parties. It argues that Eurosceptic parties have had a paradoxical effect on politicization, since mainstream parties have responded to the former's mobilizing efforts by de-emphasizing European issues rather than pursuing a confrontational strategy. This finding is corroborated by the 2019 elections, where we observe remarkably high levels of politicization in those countries where mainstream parties have been forced to open the debate around European issues.
Keywords: 300; European Parliament; elections; political parties; politicization; salience